The Effect of Sanyinjiao Accupressure on Decreasing Dysmenorrhea Pain : Scoping Review - Navantri Muliyani; Endang Koni Suryaningsih (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Purpose: Dysmenorrhea, characterized by challenging menstrual flow or menstrual pain, affects approximately half of all girls and women. Various approaches exist to alleviate the intensity of dysmenorrhea pain, among which non-pharmacological therapy stands out. Sanyinjiao acupressure (SP6) represents a non-invasive, cost-free, and time-efficient method to address discomfort during dysmenorrhea. The purpose of this research to assess the impact of Sanyinjiao acupressure (SP6) in diminishing the intensity of dysmenorrhea pain, a review of prior research is warranted. Method: This research employed a scoping review methodology, drawing upon diverse references. The search for research literature was conducted across several databases, including PubMed, Science Direct, and EBSCO, using keywords such as